Girodet's Funeral and the Romantic Drift (ARS, 2023)
Girodet's funeral is seen as a turning point in the advent of romanticism, marked by clashes involving Delécluze, Stendhal, Auger, Gros, Ingres, Delacroix. We seek to demonstrate the centrality of David's studio in the emergence of a new orientation. Until 1824 the terms were mixed up and only then there was an effort to distinguish the currents, which were in fact inflated in the political process that culminated in the July Monarchy. Less than the affirmation of a style or a thought, what was at stake was the multiplication of choices at the whim of individuals, which tended to call into question the hierarchical system of artistic practices, as observed in the criticism of Baudelaire, Heine, and Thoré.